2020
DOI: 10.1002/jcop.22343
|View full text |Cite
|
Sign up to set email alerts
|

Leadership that promotes successful implementation of community‐based mental health interventions

Abstract: Community‐based interventions (CBIs) have become an effective approach to promote mental well‐being. To increase organizational capacity and effectively deliver CBIs, leadership is crucial. The current study aims to identify leadership qualities that are facilitators of CBI implementation. This paper presents evaluation findings from a national effort emphasizing CBIs for improving the mental well‐being of men and boys in 16 local communities. The study utilized a mixed‐method design, including both examining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Many studies mention leadership as key to implementing the HPS framework ( Rowling and Samdal, 2011 ; Langford et al ., 2015 ). However, it is often not clear what constitutes an effective leadership role ( McMullen et al ., 2020 ; McNeish and Tran, 2020 ) and how it may differ between different school communities. HSCs engaged in the FLASH intervention indicated that they needed the time and support to determine what kind of leadership role was required to drive the capacity-building process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies mention leadership as key to implementing the HPS framework ( Rowling and Samdal, 2011 ; Langford et al ., 2015 ). However, it is often not clear what constitutes an effective leadership role ( McMullen et al ., 2020 ; McNeish and Tran, 2020 ) and how it may differ between different school communities. HSCs engaged in the FLASH intervention indicated that they needed the time and support to determine what kind of leadership role was required to drive the capacity-building process.…”
Section: Discussionmentioning
confidence: 99%
“…First, HSCs need professional development to become strong leaders. The importance of training leaders in (school) communities is well documented, but more research is needed on what strong leadership entails ( Whelan et al ., 2018 ; McNeish and Tran, 2020 ; Levin et al ., 2021 ). This study highlights that an HSC needs to lead the coordination of the overall process of creating a Healthy School.…”
Section: Discussionmentioning
confidence: 99%
“…First, HSCs need professional development to become strong leaders. The importance of training leaders in (school) communities is well documented, but more research is needed on what strong leadership entails [174,175,186]. This study highlights that an HSC needs to lead the coordination of the overall process of creating a Healthy School.…”
Section: Implications For Practicementioning
confidence: 87%
“…Despite the abundance of evidence for strong leadership, what constitutes an effective leadership role is not always clear [175]. Based on lessons learned during agreement among different stakeholders involved in the community [177].…”
Section: Leadership: the Healthy School-coordinator As A Change Agentmentioning
confidence: 99%
See 1 more Smart Citation